THE ASSOCIATION BETWEEN INTAKE OF ENERGY, PROTEINANDPHYSICAL ACTIVITYWITH NUTRITIONAL STATUS OF ELDERLY PEOPLE - Yoga, M. Agung Prasetya Adyana (Majority, 2015)
Abstract Becoming old is a natural processthat will be experienced by every individual. Adequate food intake and good physical activity are required pearson to maintain stable nutritional status. Factor that affect to nutritional status are energy intake, protein and physical activity. Oral health status and dietary intake contribute to nutritional status in elderly. Missing teeth cause chewing disorder that reduces quality and quantity of food intake, which finally makes the elderly have underweight nutritional status. The eldederly who live in elderly home-care usually has worse economic condition because there is no family who can take care of them anymore. The elderly often experience malnutrition that will influence their health status. Malnutrition in the elderly needs to be detected as early as possible, thus improvement can also be done as soon as possible. One way that is able to measure elderly nutritional status, nutritional food intake and physical activity in quick and eficient way is antropometri, semiquantitative food frequency questionaire and 24 hours physical activity. Keyword : elderly, energy, nutritional status, protein Abstrak Proses menua merupakanproses alamiah yang akan dialami oleh setiap individu.Asupan makanan yang cukup dan aktivitas fisik yang baik dibutuhkan seseorang untuk menjaga status gizi yang baik.Beberapa faktor yang mempengaruhi status gizi diantaranya asupan energi, protein dan aktivitas fisik.Status kesehatan mulut dan asupan makanan berkontribusi terhadap status gizi lansia.Kehilangan gigi menyebabkan gangguan pengunyahan sehingga menurunkan kualitas dan kuantitas asupan makanan yang pada akhirnya menyebabkan lansia berstatus gizi rendah. Lansia yang tinggal di panti biasanya memiliki kondisi ekonomi yang kurang baik karena sudah tidak ada keluarga yang mengurus mereka. Pada masa lansia sering terjadi kurang gizi yang dapat berpengaruh terhadap status kesehatan mereka. Lansia perlu dideteksi status gizi secara dini agar dapat dilakukan perbaikan secepat mungkin. Alat yang dapat digunakan untuk mengukur status gizi lansia, asupan makanan dan aktivitas fisik lansia yaitu dengan antropometri, kuesioner semikuantitatif frekuensi makanan, dan 24 jam recall aktivitas fisik. Kata Kunci : energi, kuesioner, lanjut usia, protein, status gizi